Exploring natural language understanding in robotic interfaces - Ioannis Giachos; Evangelos C. Papakitsos; Georgios Chorozoglou (Universitas Ahmad Dahlan, 2017)
Natural Language Understanding is a major aspect of the intelligence of robotic systems. A main goal of improving their artificial intelligence is to allow a robot to ask questions, whenever the given instructions are not complete, and also by using implicit information. These enhanced communicational abilities can be based on the voids of an output data structure that corresponds to a systemic-semantic model of language communication, as grammar formalism. In addition, the enhancing process also improves the learning abilities of a robot. Accordingly, the presented herein experimental project was conducted by using a simulated (by a plain PC) robot and a simple constructed language that facilitated semantic orientation.